2017
DOI: 10.1021/acsomega.6b00523
|View full text |Cite
|
Sign up to set email alerts
|

Naphthalenediimide-Linked Bisbenzimidazole Derivatives as Telomeric G-Quadruplex-Stabilizing Ligands with Improved Anticancer Activity

Abstract: Human telomeric G-quadruplex DNA stabilization has emerged as an exciting novel approach for anticancer drug development. In the present study, we have designed and synthesized three C2-symmetric bisubstituted bisbenzimidazole naphthalenediimide (NDI) ligands, ALI-C3, BBZ-ARO, and BBZ-AROCH2, which stabilize human telomeric G-quadruplex DNA with high affinity. Herein, we have studied the binding affinities and thermodynamic contributions of each of these molecules with G-quadruplex DNA and compared the same to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 60 publications
(113 reference statements)
0
12
0
Order By: Relevance
“… 6 Apoptosis is an efficient programmed regulation of cellular homeostasis defined by cell biology. 7 Reactive oxygen species (ROS) act as a crucial factor by working as a messenger in a cellular-signaling system to alarm apoptosis. 8 The equilibrium of ROS and the antioxidant is a prime factor, and any alteration of these two causes various cellular harms, leading to inflammatory diseases and carcinogenesis.…”
Section: Introductionmentioning
confidence: 99%
“… 6 Apoptosis is an efficient programmed regulation of cellular homeostasis defined by cell biology. 7 Reactive oxygen species (ROS) act as a crucial factor by working as a messenger in a cellular-signaling system to alarm apoptosis. 8 The equilibrium of ROS and the antioxidant is a prime factor, and any alteration of these two causes various cellular harms, leading to inflammatory diseases and carcinogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Sur et al [93] synthesized three bi‐substituted bis‐benzimidazole naphthalene diimide ligands, that stabilized the human g‐quadruplex DNA (telomeric) with strong (high) affinity. Studies revealed that treatment with compound 71 resulted in considerable inhibition of telomerase activity (IC 50 = 4.56 μM) and induced apoptosis in cancer cell‐lines with minimal cytotoxic activity in normal HEK293T cells.…”
Section: Benzimidazole As Target Oriented Anticancer Agentsmentioning
confidence: 99%
“…Compound 16 was also found to inhibit tumor growth in a mouse xenograft model of cervical squamous cancer [ 216 ]. A disubstituted bisbenzimidazole naphthalenediimide (NDI) ligand BBZ-ARO, was reported to possess high telomeric G4 affinity, which could inhibit telomerase enzyme activity and caused G2/M arrest subsequently inducing apoptosis in cells with a good therapeutic index [ 217 ]. Divalent cationic naphthalene diimide ligands have been shown to selectively bind with telomeric G4 ligand and some of them could specifically kill cancer cells while having very less effect on normal cells [ 218 ].…”
Section: Targeting Telomeric Components In Cancermentioning
confidence: 99%